2019
DOI: 10.1016/j.tranon.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization of Next-Generation RNA Sequencing-Based MammaPrint® and BluePrint® Kit at University Hospitals Leuven and Curie Institute Paris

Abstract: A previously developed and centrally validated MammaPrint® (MP) and BluePrint® (BP) targeted RNA next-generation sequencing (NGS) kit was implemented and validated in two large academic European hospitals. Additionally, breast cancer molecular subtypes by MP and BP RNA sequencing were compared with immunohistochemistry (IHC). Patients with early breast cancer diagnosed at University Hospitals Leuven and Curie Institute Paris were prospectively included between September 2017 and January 2018. Formalin-fixed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Currently, Agendia has developed an FFPE-based next-generation sequencing kit for the implementation of 70-GS in a decentralized setting, which allows central laboratories to process the samples within country borders [24]. Recently reported validation results are promising and select laboratories in Belgium and Germany have implemented this process already [25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Agendia has developed an FFPE-based next-generation sequencing kit for the implementation of 70-GS in a decentralized setting, which allows central laboratories to process the samples within country borders [24]. Recently reported validation results are promising and select laboratories in Belgium and Germany have implemented this process already [25].…”
Section: Discussionmentioning
confidence: 99%
“…Solutions to these limitations are not generalizable and may differ from one region to another [ 130 ]. To ensure consistency and accuracy, some molecular profiling assessments may only be available at specialized centers of excellence, whereas the cost of specialized laboratory infrastructures may limit the testing capabilities of local centers [ 130 , 131 ]. However, reductions in the cost of specialist equipment, as well as the development of kit-based genomic, transcriptomic, and proteomic assays with robust bioinformatic algorithms that mitigate the need for specialized expertise, may facilitate the implementation of decentralized molecular diagnostics and increase patient access to testing [ 130 , 131 , 132 ].…”
Section: Future Directions For Molecular Profiling Of Patients With C...mentioning
confidence: 99%
“…To ensure consistency and accuracy, some molecular profiling assessments may only be available at specialized centers of excellence, whereas the cost of specialized laboratory infrastructures may limit the testing capabilities of local centers [ 130 , 131 ]. However, reductions in the cost of specialist equipment, as well as the development of kit-based genomic, transcriptomic, and proteomic assays with robust bioinformatic algorithms that mitigate the need for specialized expertise, may facilitate the implementation of decentralized molecular diagnostics and increase patient access to testing [ 130 , 131 , 132 ]. Whether testing is centralized or localized, clinical diagnostics will benefit from the digital exchange of molecular profiling data that can be viewed by a multidisciplinary team of experts (such as molecular tumor boards) to derive accurate and timely diagnoses [ 5 , 90 ].…”
Section: Future Directions For Molecular Profiling Of Patients With C...mentioning
confidence: 99%
“…Recently, the MammaPrint® and BluePrint® RNA sequencing test was found to be equivalent to the clinically validated microarray test [68]. It was also demonstrated that the MammaPrint RNA-sequencing test can be used as a decentralized platform with results equivalent to those derived from the predicated diagnostic device [68, 69]. Independent intra-assay reproducibility was also shown for the Prosigna® and EndoPredict® assays [70, 71].…”
Section: Comparison Of Different Multigene Signaturesmentioning
confidence: 99%